A218 EVALUATION OF IBD SPECIALTY CARE IN NOVA SCOTIA: THE REFERRING PHYSICIAN PERSPECTIVE. (1st March 2018) - Burns, E E; Heisler, C; Kits, O; Veldhuyzen van Zanten, S; Jones, J
Abstract: Background: The incidence and prevalence rates of Inflammatory Bowel Disease (IBD) in Canada have been observed to be amongst the highest globally, with the highest observed estimates in Nova Scotia (NS). Excessive wait times for outpatient consultations is a well-documented problem. As increased wait times lead to negative outcomes for IBD patients, it is crucial that a thorough understanding of access to care is obtained by engaging multiple stakeholders including patients, referring physicians, specialist physicians, and administrative personnel. Aims: The study aim was to identify barriers in access to IBD care for referring physicians and their patients. Methods: This was a mail-out survey between July and October 2017 of a representative sample of general practitioners (GPs) referring to GI IBD specialty care in NS. Stratified sampling was done to ensure geographic representativeness of the sample. The survey incorporated social exchange theory and included a non-conditional incentive to maximize response rates. The questionnaire consisted of five sections: 1) demographic information (e.g. sex, age, patient load); 2) geographic information (e.g. urban versus rural); 3) referral processes (e.g. number of referrals sent to GI, communication between GP and GI offices); 4) patient wait times (e.g. how many patients on wait list); 5) referral process satisfaction. Descriptive analyses were carried out using Stata software. The project was approved by the NS Health Authority Research Ethics board. Results: This survey is still in progress. A total of 634 surveys were mailed out, and thus far 145 were returned (23%). Mean age was 48 years (29 to 77 years), mean number of years in practice was 18 (1 to 50 years). Sixty-eight percent (n=99) worked in a private practice setting, and 46 (44%) in an urban setting. Thirty-one percent of respondents did not have access to IBD specialty care in their community, but the majority (84%) had access in their health zone. Over half (57%) of respondents were either dissatisfied or very dissatisfied at the current referral process. Forty-one percent felt the current referral process was either inefficient or very efficient. Respondents identified the following as being access barriers: 1) perceived inequity in access to GI for rural compared to urban areas, 2) need to increase number of GIs, and 3) need to create a centralized referral and triage process for the whole province. Conclusions: The results show wait times for IBD patients are a significant problem and there is major dissatisfaction among GPs about the referral process. Identification of barriers to IBD specialty care can lead to informed system redesign with goals of improving access to GI specialist IBD care, improving access efficiency, overcoming access inequities for patients and referring physicians and ultimately improving health outcomes. Funding Agencies: CIHRNova Scotia Health Authority Research Fund